Contribuição para os usuários de sistemas CAD/CAM/CNC em operação de fresamento de topo em aço para moldes e matrizes - Costa, Gustavo Guilherme dos Santos (2011)
The increased in the demand for plastic products and the need for reduction manufacturing times, and the growing dependence of man on the computer in present day, especially in manufacturing activities, has resulted in constant research of technological developments in order to supply these needs. In dies and molds manufacturing industry for plastic injection requiring machining operations such as (milling, drilling and polishing, among others), is increasing dependence by computer systems, such as CAD/CAM. This technology helps in the manufacturing steps, provides fast and high accuracy in the manufacturing of complex geometries. Therefore, to understand and to use efficiently these resources that aided in manufacturing are of enormous importance for the optimization of a production process. In this context, this work presents a study on the use of resources programming CAD/CAM in milling operation of cavities steel VP50 with inserts cemented carbide with ball nose. The influence of two types of interpolation (linear and circular) and tolerances bands (0.05 mm and 0.1 mm) that define the tool path for machining of a cavity that has a similar form the a mold of a battery cover cell phone. As output variables evaluated were machining time, the number of lines of the program, the parameters of surface roughness (Ra, Rq, Rz) of parts, the radius of curvature, form deviation of any line profile and the tool wear. The results showed that, from the statistical point of view (ANOVA), none of the conditions of interpolation and tolerance employed significantly influenced the values of surface roughness in form deviation of any line and tool wear. Linear interpolation with tolerance of 0.1 mm was most viable for the production of such cavity in the conditions investigated because the produced good finish, low tool wear and machining time is shorter.